Easy determination of radiation absorption in brain tissue from mobile phones using finite element method - Yakubu, Abu Bakar; Abbas, Zulkifly; Yunusa, Zainab (Scientific Research Publishing, 2019)
ZULKIFLY BIN ABBAS////// Abu Bakar Yakubu,Zainab Yunusa